Strength and Conditioning : A Concise Introduction - Cissik, John M. (Routledge, 2020)
"Strength and Conditioning: A Concise Introduction offers a concise but comprehensive overview of training for athletic performance. Introducing essential theory and practical techniques in all of the core areas of athletic training, the book clearly demonstrates how to apply fundamental principles in putting together effective real-world training programs. This book encourages students and professionals to think critically about their work and to adopt an evidence-based approach. It explains the inter-dependence of aspects of training such as needs analysis, assessment, injury, competition level, athlete age and program design, and it fully explains how those aspects should be integrated. Strength and Conditioning is an accessible, engaging and reflective introduction to the theory and application of strength and conditioning programs. Including clear step-by-step guidance, suggestions for further reading, and detailed sport-specific examples, this is the perfect primer for any strength and conditioning course or for any professional trainer or coach looking to refresh their professional practice. Included in the second edition are in-depth descriptions of free weights, kettlebells, heavy ropes, speed, agility, horizontal force production training, as well as updated research from the strength and conditioning field. Programming chapters and real-world programs provide examples of how to incorporate all the modern strength and conditioning tools. This is the perfect primer for any strength and conditioning course or for any professional trainer or coach looking to refresh their professional practice"--